2013
DOI: 10.1200/jop.2012.000796
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Diagnostic Breast Cancer Imaging: Variation and Patterns of Care in Washington State

Abstract: Use of breast MRI and other advanced imaging is increasing among patients newly diagnosed with breast cancer; individual patient and insurance-related factors are associated with receipt of these imaging tests. Whether use of diagnostic advanced imaging affects outcomes such as re-excision, cancer recurrence, mortality rates, and costs of breast cancer treatment remains to be determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…Similar to another study, performed in the United States, 23 we have shown that a range of patient, tumour and treatment characteristics are associated with increased imaging use, which may be useful in improving adherence. For example, certain adverse tumour characteristics such as stage, involvement of the axillary lymph nodes, lymphovascular invasion, negative HER2 status and tumour grade were all associated with increased utilization of imaging.…”
Section: Discussionsupporting
confidence: 63%
“…Similar to another study, performed in the United States, 23 we have shown that a range of patient, tumour and treatment characteristics are associated with increased imaging use, which may be useful in improving adherence. For example, certain adverse tumour characteristics such as stage, involvement of the axillary lymph nodes, lymphovascular invasion, negative HER2 status and tumour grade were all associated with increased utilization of imaging.…”
Section: Discussionsupporting
confidence: 63%
“…We linked health plan enrollment and utilization files from three commercial health plans (Regence Blue Shield, Premera Blue Cross, and Uniform Medical Plan), one mixed-model health delivery system (Group Health Cooperative) and two publically funded health care programs (Medicaid and Medicare) with the western Washington Surveillance Epidemiology and End Results registry [ 25 ]. The linkage identified all adult (age: 18 years or older) females diagnosed with an incident invasive breast carcinoma between 2002 and 2008.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the well-established guidelines for MRI screening in patients with an inherited predisposition to breast cancer, 9 to our knowledge, there are no guidelines for MRI use in patients with newly diagnosed breast cancer; nevertheless, a report from Western Washington State's Surveillance, Epidemiology, and End Results (SEER) registry demonstrated that 27% of 9196 women with breast cancer underwent MRI for staging or treatment planning between 2002 and 2009, 10 and by 2009, 46% of women underwent perioperative breast MRI. MRI use varied significantly based on age, with 45% of women aged 18 years to 40 years undergoing an MRI compared with 10% of those aged 81 years (P < .001).…”
Section: Current Mri Usementioning
confidence: 99%